Improved Torque Control Performances Using Torque Error Modulator For Multilevel Inverter Based DTC Induction Motors - Sundram, Ramahlingam; Auzani, Jidin; Azrita, Alias; Logan Raj, Lourdes Victor Raj; Atikah, Razi (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
This paper presents the advantage of Torque Error Modulator (TEM) implementation in conventional Direct Torque Control (DTC) of 3-phase induction motor with 3-level Cascade H-bridge Multilevel Inverter (CHMI). The DTC system is known to offer fast decoupled control of torque and flux via a simple control structure. Nevertheless, DTC system has two major drawbacks, which are the variable inverter switching frequency and high torque ripple. The major factor contributes to these problems are the usage of hysteresis based comparators in controlling the output torque. The implementation of TEM in DTC provides solution to these problems while retaining the simple control structure of conventional DTC. The combination usage of 3-level CHMI with TEM can further minimize the output torque ripple of 3-phase DTC system by providing greater number of vectors. The 3-level CHMI of 3-phase system provides 18 active voltage vectors where each vector may give different effect on controlling performance of 3-phase induction machine in various torque demands. In order to verify the feasibility of the proposed method experimentation, the proposed method compared with convention DTC system via simulation and experiment results.